Study of T-cell immunity, interferogenesis, inflammatory mediators in children with Varicella zoster virus infection - O. A. Saburova; D. M. Sobchak; K. A. Otmakhova (LLC "Diagnostics and Vaccines", 2022)
The aim of the study. Determination of immune response mediators in patients with infection caused by the Varicella Zoster virus with various clinical and laboratory parameters.Materials and methods. Determination of VZV DNA by the polymerase reaction method. The blood content of proinflammatory mediators was assessed using the ELISA method using monoclonal antibodies (Protein contour, Petersburg).Research result. In patients with VZV the content of INF-α, INF-γ, CD-8+ was significantly lower than in patients with a typical form of the disease. In patients with a typical course of the disease, the DNA of the virus was less often determined.Discussion. In patients with pustular chickenpox, the level of IL-1β and CD-4+ was significantly lower than in the typical course of the disease.Conclusions. A decrease in the content of immune response mediators and indicators of cellular immunity in children with chickenpox is an indication for vaccination.